Evolution of the Beckwith-Wiedemann syndrome region in vertebrates - Paulsen, Martina; Khare, Tarang; Burgard, Christopher; Tierling, Sascha; Walter, Jörn (Genome Research, 2005)
In the animal kingdom, genomic imprinting appears to be restricted to mammals. It remains an open question how structural features for imprinting evolved in mammalian genomes. The clustering of genes around imprinting control centers (ICs) is regarded as a hallmark for the coordinated imprinted regulation. Hence imprinted clusters might be structurally distinct between mammals and nonimprinted vertebrates. To address this question we compared the organization of the Beckwith Wiedemann syndrome (BWS) gene cluster in mammals, chicken, Fugu (pufferfish), and zebrafish. Our analysis shows that gene synteny is apparently well conserved between mammals and birds, and is detectable but less pronounced in fish. Hence, clustering apparently evolved during vertebrate radiation and involved two major duplication events that took place before the separation of the fish and mammalian lineages. A cross-species analysis of imprinting center regions showed that some structural features can already be recognized in nonimprinted amniotes in one of the imprinting centers (IC2). In contrast, the imprinting center IC1 is absent in chicken. This suggests a progressive and stepwise evolution of imprinting control elements. In line with that, imprinting centers in mammals apparently exhibit a high degree of structural and sequence variation despite conserved epigenetic marking.